REPRESENTATION OF POPULAR ISLAM IN DIGITAL SPACE: RELIGIOUS TOLERANCE IN SUFI EXPRESSIONS ON THE INSTAGRAM ACCOUNT “_zukkk” - Rahmah, Farida Novita; Nisok, Siti Roisadul; Ma’rief, Muammar Iqbal; Hisyam Taurus, Zainun Nur (Balai Penelitian dan Pengembangan Agama Makassar, 2025)
The development of digital technology and social media has transformed the landscape of religious practices, particularly in the context of Popular Islam in Indonesia. This article examines the representation of Popular Islam through Sufi expressions on the Instagram account _zukkk, focusing on how visually Sufi-inspired representations convey messages of tolerance and religious inclusivity in the digital space. Charles Sanders Peirce’s semiotic approach is used to analyze the visual meanings in these digital artworks, while Stuart Hall’s theory of representation is applied to understand how these meanings are constructed and negotiated within social and media contexts. The analysis shows that the Sufi expressions on _zukkk are not merely artistic works, but a social construction that emphasizes the values of moderation and openness in Popular Islam. Sufism, as the spiritual foundation of this expression, also helps shape an inclusive and tolerant view of religion, engaging in interfaith dialogue amidst the dominant narratives of conservative and digital religiosity. This study also highlights the important role of social media as a space for negotiating meaning, where visual representation becomes an effective medium for spreading spiritual and social messages. This research contributes to the study of Popular Islam and digital media by presenting Sufism as an inclusive discourse that is visually represented and socially produced within the digital realm. These findings encourage a new understanding of the relationship between art, spirituality, and religious tolerance in the complex and diverse virtual world.